Mosque in China: architectural features and functions - Dautibieke, D.; Bajtenova, N. Zh.; Mukan, N.; Mukan, N. (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2018)
The authors analyze architectural features and functionsofmosques in China. The mosque in the Muslim community of China is the focus of different (religious, social, political, economic, cultural) aspects of life and activities of Muslims. The architectural appearance and arrangement of mosques in China incorporates both features, inherent to religious buildings of Islam and some features of Chinese national culture. Key words: Mosque, architecture, function, religion, Islam.